(untitled)
Background: Many differences are observed with respect to hospital outcome among demyelinating and axonal type of Guillain-Barre Syndrome. Objective: Aims of this study was to compare the hospital outcome at discharge among demyelinating and axonal type of Guillain-Barre syndrome. Methodology: This prospective observational study was conducted from Oct, 2017 to September, 2018 at the National Institute of Neurosciences and Hospital, Dhaka, Bangladesh. All demyelinating and axonal variant of GBS, presented within 2 weeks were included in this study. The clinical parameters were taken for baseline analysis. Outcomes were measured at discharge by MRC score, length of hospital and ICU stay, recovery and death. Results: Out of 108 GBS cases 55 (50.9%) demyelinating & 53 (49.1%) were axonal subtype. Mean age; 40.20 ± 16.26 vs. 32.43 ± 14.93 years in demyelinating vs. axonal cases (p=0.011). Symptom onset and nadir of weakness are quicker in axonal than demyelinating cases (8.47±4.97 vs. 12.36±7.94) (p=0.017) and (6.7 ± 4.5 vs. 8.36 ± 4.59) (p=0.022)] days. Baseline MRC score were (18.04±9.85 vs 12.94±9.91) (p=0.009) demyelinating vs. axonal cases. At discharge, Mean MRC score, length of hospital stay, length of ICU stay were, (22.15±9.38 vs 17.39±9.46; p=0.013); (15.13±17.60 vs 23.58±23.55) days (p=0.038)